Characterization Analysis Of The Character In Short Story Entitled The Lottery - Ni Kadek Dwina Cantika Gayatri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research is based on an analysis of an American short story entitled The Lottery by Shirley Jackson. The purpose of this analysis is to examine and categorize the characterization of the character in the short story. The methods applied to analyze the data in this study is a qualitative method to describe in words the examination of the short story based on the characterization. The data source is collected through documentation and note-taking processes. For the results of this analysis the character in the short story classified into several types and detailed classifications of each character's traits, actions, and roles within the context of the narrative.